2013
DOI: 10.1371/journal.pone.0078137
|View full text |Cite
|
Sign up to set email alerts
|

Collecting Duct Carcinomas Represent a Unique Tumor Entity Based on Genetic Alterations

Abstract: Collecting duct carcinoma (CDC) is a rare renal neoplasm that is associated with poor prognosis due to its highly aggressive course and limited response to immuno- or chemotherapy. Histologically, CDC is defined as a subtype of renal cell carcinomas, but in some cases, it is difficult to differentiate from urothelial carcinomas (UC). Therefore the aim of this study was to determine genetic alterations of CDC in comparison to that of urothelial carcinomas of the upper urinary tract (UUT-UC) to clarify the histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Collecting duct carcinoma (CDC) or Bellini duct carcinoma remains a highly aggressive RCC arising from the renal collecting tubules. A recent specific gene expression signature showed that CDC appears to be a unique entity among kidney cancers [11]. Moreover, these tumours are characterised by an immune profile with an average of 22% of tumour-infiltrating lymphocytes [12].…”
Section: Pathology Assessmentmentioning
confidence: 99%
“…Collecting duct carcinoma (CDC) or Bellini duct carcinoma remains a highly aggressive RCC arising from the renal collecting tubules. A recent specific gene expression signature showed that CDC appears to be a unique entity among kidney cancers [11]. Moreover, these tumours are characterised by an immune profile with an average of 22% of tumour-infiltrating lymphocytes [12].…”
Section: Pathology Assessmentmentioning
confidence: 99%
“…Perhaps most interestingly, the patterns of gene expression in CDC were most like those of the distal convoluted tubules of the nephron, providing support for the hypothesis of origin in the distal nephron. The question of molecular overlap with upper tract urothelial carcinoma has also been addressed from the standpoint of CGH, where substantially different recurrent DNA losses and gains were observed in CDC compared to urothelial carcinoma . We note the caveat in all of these results that it is unclear whether or how FH‐deficient carcinoma was excluded from the CDC cases studied.…”
Section: Collecting Duct Carcinoma − Upon Increasingly Rigorous Exclumentioning
confidence: 84%
“…The question of molecular overlap with upper tract urothelial carcinoma has also been addressed from the standpoint of CGH, where substantially different recurrent DNA losses and gains were observed in CDC compared to urothelial carcinoma. 79 We note the caveat in all of these results that it is unclear whether or how FH-deficient carcinoma was excluded from the CDC cases studied. Indeed two of the CDCs in the latter CGH study 79 seem to have harbored (albeit broad) chromosomal losses involving the area of the FH locus.…”
Section: Collecting Duct Carcinoma à Upon Increasingly Rigorous Exclumentioning
confidence: 92%
See 1 more Smart Citation
“…Associated chromosomal abnormalities are losses of various chromosomal regions on chromosomes: -1p, -8p, -9p, and gains on chromosome at-13q (ref. 34 ).…”
Section: Collecting-duct Carcinomamentioning
confidence: 99%